Attenuated cardiac post-ischemic injury and endothelial dysfunction by stimulation of soluble guanylyl cyclase in red blood cells from patients with type 2 diabetes. (14th October 2021) - Jiao, T; Zhou, Z; Mahdi, A; Tengbom, J; Tratsiakovich, Y; Yang, J; Pernow, J
Abstract: Background: Reduced bioavailability of nitric oxide (NO) contributes to ischemic heart disease in type 2 diabetes (T2D). Red blood cells (RBCs) are known to produce NO bioactivity and to contain a functional soluble guanylyl cyclase (sGC) that is activated by NO. Recent studies revealed that RBCs from patients with T2D exacerbates ischemia-reperfusion (I/R) injury and induces endothelial dysfunction via a mechanism that is dependent on reduced export of NO bioactivity from RBCs. It remains unknown whether stimulation of sGC in RBCs from patients with T2D protects against myocardial I/R injury and endothelial dysfunction. Purpose: To test the hypothesis that stimulation of sGC in RBCs from T2D patients protects against myocardial I/R injury and improves endothelial function. Methods: RBCs collected from T2D patients and healthy subjects were incubated with vehicle or the sGC stimulator CYR715 before being administered to isolated Langendorff-perfused rat hearts subjected to 25 min global ischemia and 60 min reperfusion. Left ventricular developed pressure (LVDP) and infarct size were determined. In addition, isolated rat aortic rings were incubated with RBCs subsequent determination of endothelium-dependent relaxation (EDR). Results: Administration of RBCs from T2D patients impaired post-ischemic recovery of LVDP and induced endothelial dysfunction in comparison with RBCs from healthy subjects (P<0.001). Pre-incubation of RBCs from patients with T2D with CYR715 prior to administration to the isolated heart enhanced the recovery of LVDP (Fig.1A), reduced infarct size (Fig.1B), and attenuated endothelial dysfunction (Fig.1C). CYR715 did not induce cardioprotection in the absence of RBCs. The sGC inhibitor ODQ did not significantly affect cardiac recovery per se but totally abolished the protective effect of CYR715 (Fig.1A). Conclusions: Stimulation of sGC in RBCs from patients with T2D protects against cardiac I/R injury and prevents development of endothelial dysfunction. Stimulation of the NO-sGC pathway in RBCs appears to be an attractive therapeutic strategy to prevent cardiovascular injury in T2D. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Heart and Lung Foundation, the Swedish Research Council